Indigenous-led toxic tours opening pathways for (re)connecting to place, people and all creation - Bobbie Chew Bigby; Rebecca Jim; Earl Hatley (Australian Journal of Environmental Education)
Home to nine Tribal Nations, the northeastern corner of Oklahoma (US) is a place of immense resilience, cultural beauty and attachment to place. Horrifically, however, this same area is also home to massive environmental assaults that have occurred as a result of decades of lead and zinc mining. The improperly managed mine waste that has accumulated since the late 1800s now severely contaminates the water, land and air, having adverse impacts on the health of the ecosystem and the local human community alike. Leading the fight for cleanup and support of place and people since 1997 is the non-profit organisation called Local Environmental Action Demanded (LEAD Agency). One of LEAD’s primary tools for education and advocacy has been leading toxic tours across these harmed lands and waters. This contribution draws upon the nearly three decades of toxic tours that Rebecca and Earl have led by sharing key stories and experiences of important sites visited along the way, offering a snapshot of toxic tour experience. Drawing on Indigenous storywork and autoethnographic methodologies, this contribution aims to spotlight the potential of Indigenous-led toxic tours for helping to (re)connect people — both locals and visitors — to place and a responsibility of stewardship.